A Hierarchical Model of a Vector Nash Equilibrium Search in a Control Problem under Conflict and Uncertainty - Vladimir A. Serov; Evgeny M. Voronov (Engineering Proceedings, 2023)
A hierarchical model of a vector Nash equilibrium search under uncertainty is developed. The sufficient conditions for a vector Nash equilibrium of a noncooperative game under uncertainty are formulated, which can be used as a criterion to achieve the required degree of nonquilibrium for an acceptable solution to the problem of multi-object multicriteria systems’ control optimization under conflict and uncertainty.